SOFIA/upGREAT Imaging Spectroscopy of the [C ii] 158 μm Fine-structure Line toward the Sgr A Region in the Galactic Center - A. I. Harris; R. Güsten; M. A. Requena-Torres; D. Riquelme; M. R. Morris; G. J. Stacey; J. Stutzki; Y. Okada; E. Chambers; M. Mertens; C. Fischer (The Astrophysical Journal)
We present SOFIA/upGREAT velocity-resolved spectral imaging and analysis of the λ 158 μ m [C ii ] spectral line toward the central 80 by 43 pc region of the Central Molecular Zone of the Galaxy. The field we imaged with 14″ (0.6 pc) spatial and 1 km s ^−1 spectral resolution contains the circumnuclear disk (CND) around the central black hole Sgr A*, the neighboring thermal Arched Filaments, the nonthermal filaments of the Radio Arc, and the three luminous central star clusters. [C ii ] traces emission from the CND’s inner edge to material orbiting at a distance of approximately 6 pc. Its velocity field reveals no sign of inflowing material nor interaction with winds from the Sgr A East supernova remnant. Wide-field imaging of the Sgr A region shows multiple circular segments, including the thermal Arched Filaments, that are centered on a region that includes the Quintuplet cluster. We examine the possibility that the Arched Filaments and other large-scale arcs trace transient excitation events from supernova blast waves. Along the Arched Filaments, comparisons among far-infrared fine-structure lines show changes in the ionization state over small scales and that high-excitation lines are systematically shifted in position from the other lines. These also point to transient fast winds that produce shocks on the surface of the Arches cloud to produce additional local ultraviolet (UV) radiation to excite the Arched Filaments on a cloud surface illuminated by UV from hot stars.